- PERLINDUNGAN KONSUMEN ATAS PENIMBUNAN OBAT PADA MASA PANDEMI: - - Yustio Rony Saputro; N.G.N Renti Maharaini Kerti (Faculty of Law, Universitas Trisakti, 2023)
Shortage of goods during the pandemic such as basic necessities, masks, hand sanitizers, vitamins, and medicines has resulted in significant price increases. This has become an opportunity for unscrupulous business actors to seek profit, as done by PT. ASA who hoarded medicines. The main problem in this research is role of the government in relation to the hoarding of Azithromycin by PT. Atlas Sukses Abadi and the accountability of PT. Atlas Sukses Abadi Indonesia as a business actor for the act of hoarding Azithromycin. This research was conducted using normative juridical approach, descriptive-analytical in nature, using qualitative analysis of secondary data, and drawing conclusions through deductive method. It can be concluded that the Government, in dealing with the hoarding of Azithromycin, has carried out its duties in accordance with the regulations. PT. Atlas Sukses Abadi is responsible for the act of hoarding the medicine, as business actors have criminal liability according to the Consumer Protection Law, namely Article 62 in conjunction with Article 61 and Article 10 of Law No. 8 of 1999 on Consumer Protection, Article 14 in conjunction with Article 5 section (1) of Law No. 4 of 1984 on Infectious Disease Outbreaks, and Article 107 in conjunction with Article 29 section (1) of Law No. 7 of 2014.